Evaluation & Management of Functional Abdominal Pain in Children - Malinak, DO, Robert (Osteopathic Family Physician, 2017)
Non-organic or functional, abdominal pain is pain that exists free of a pathologic state. This is the most common type of chronic abdominal pain in children. It interrupts a child’s normal daily activities and causes stress and anxiety amongst families. In the past, it has been poorly treated due to misconceptions and inadequate knowledge of evaluation and application of treatment. A proper history and physical evaluation of the abdominal pain is required for accurate diagnosis. ROME IV criteria is the diagnostic criteria used for children once organic chronic abdominal pain is ruled out. Treatments that are available for use in non-organic chronic abdominal pain in children consist of behavioral therapies, diet changes, and recently approved pharmaceutical medications.